Respuesta :

Answer:[tex]ln(x^{\frac{1}{4}}y^{\frac{1}{2}}z^{\frac{2}{3}})[/tex]

Step-by-step explanation:

Formula:

[tex]k\times ln(a)=ln(a^{k})[/tex]

[tex]ln(a)+ln(b)=ln(ab)[/tex]

[tex]ln(a)-ln(b)=ln(\frac{a}{b})[/tex]

[tex]\frac{1}{4}\times ln(x)=ln(x^{\frac{1}{4}})[/tex]

[tex]\frac{-1}{2}\times ln(x)=ln(x^{\frac{-1}{2}})[/tex]

[tex]\frac{2}{3}\times ln(x)=ln(x^{\frac{2}{3}})[/tex]

Working:

So,[tex]\frac{1}{4}ln(x)-\frac{1}{2}ln(y)+\frac{2}{3}ln(z)=ln(x^\frac{1}{4})-ln(y^\frac{-1}{2})+ln(z^\frac{2}{3})[/tex]

=[tex]ln(\frac{x^\frac{1}{4}}{y^{\frac{-1}{2}} } )+ln(z^{\frac{2}{3}})[/tex]

=[tex]ln(x^\frac{1}{4}}{y^{\frac{1}{2}}z^{\frac{2}{3} })[/tex]

ACCESS MORE